A case-control, multicentre study of consecutive patients with COVID-19 and acute (myo)pericarditis: incidence, risk factors, clinical characteristics and outcomes. Issue 5 (18th March 2022) - Mirò, Òscar; Sabaté, Manel; Jiménez, Sònia; Mebazaa, Alexandre; Martínez-Nadal, Gemma; Piñera, Pascual; Burillo-Putze, Guillermo; Martín, Alfonso; Martín-Sánchez, Francisco Javier; Jacob, Javier; Alquézar-Arbé, Aitor; García-Lamberechts, Eric Jorge; et al.
Abstract : Objective: To estimate incidence, risk factors, clinical characteristics and outcomes of acute (myo)pericarditis (AMP) in patients with COVID-19. Methods: Case-control, retrospective review, consecutive case inclusion performed in 62 Spanish EDs. All COVID-19 patients with AMP (cases) were compared in clinical characteristics and outcomes with COVID-19 without AMP (control group A) and non-COVID patients with AMP (control group B). We estimated unadjusted standardised incidence (SI, not adjusted by population's age/sex) of AMP in COVID-19 and non-COVID populations (per 100 000/year). Results: We identified 67 AMP in COVID-19 patients (SI=56.5, OR with respect to non-COVID patients=4.43, 95% CI=3.98 to 4.94). Remarkably, COVID-19 cases presented with chest pain less frequently than non-COVID patients and had less typical ECG changes, higher NT-proBNP (N-terminal prohormone of brain natriuretic peptide), more left and right ventricular dysfunction in echocardiography and more need of inotropic/vasopressor drugs. Admission to intensive care was higher than control group A (OR=3.22, 95% CI=1.43 to 7.23), and in-hospital mortality was higher than control group B (OR=7.75, 95% CI=2.77 to 21.7). Conclusion: AMP is unusual as a form of COVID-19 presentation (about 1‰ cases), but SI is more than fourfold higher than non-COVID population, and it is less symptomatic, more severe and has higher in-hospital mortality; therefore, rapid recognition, echocardiographic assessment of myopericardial inflammation/dysfunction and treatment with vasoactive drugs when needed are recommended in AMP in patients with COVID-19.